SYSTEMATIC LITERATURE REVIEW: PENGARUH AUDIT DELAY DAN KUALITAS AUDIT TERHADAP HARGA SAHAM DENGAN GOOD CORPORAATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Juang, Juang; Trinandari Prasetya Nugrahanti (Juremi: Jurnal Riset Ekonomi, 2026)
This study aims to systematically synthesize empirical evidence on the effect of audit quality and audit delay on stock prices, with Good Corporate Governance (GCG) as a moderating variable. A Systematic Literature Review (SLR) was conducted on 20 relevant national and international studies. The findings indicate that audit quality positively affects stock prices by enhancing the credibility and reliability of financial information. In contrast, audit delay is generally perceived as a negative signal that increases information uncertainty and reduces investor confidence. Furthermore, GCG particularly through the role of the audit committee moderates these relationships by strengthening the positive impact of audit quality and mitigating the negative effect of audit delay on stock prices. This study contributes to the audit and capital market literature by integrating signaling theory and agency theory perspectives.